Check-in, departure and arrival times: Air cargo in Southern Africa? - Bianka Dettmer; Peter Draper; Andreas Freytag (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
In this paper we develop a methodology which is based on two important criteria - sensitivity in delivery time and value-to-weight ratio - to classify products relevant for air transport. Detailed trade data by mode of transport are used to check the loading of an average airplane between South Africa and the European Union. The product classification is applied to evaluate the potential for air cargo transport in Southern Africa. We find that especially export of products with high and medium air cargo relevance grew much faster than exports of bulky goods and non air cargo products. South Africas most prominent export products to industrialized countries consist of diamonds, gold and platinum (HS71) which, however, are so precious that they tend to be transported in the hand baggage of a business or security person, because they leave the loading weight of an average airplane almost unaffected. When correcting South Africas trade for these invisible outliers in the loading freight we find that South Africa exports a much larger share of products with high air cargo relevance to its SADC partners than to industrialized countries. The results indicate that air cargo seems to be valuable option to overcome trade barriers associated with poor land transport infrastructure and corruption.
Keywords: F10; F14; F15; L93; 330; air transport; intra-African trade; time sensitivity; trade cost